Novel Technique For PAPR and Average Power Reduction In OFDM Scheme - Sa’d, Adnan Haider Yusef; Wahab, Aeizaal Azman Abdul (WARSE, 2019)
Orthogonal frequency division multiplexing (OFDM) is a multicarrier modulation technique that relies on orthogonality feature to increase transmission data rate while enhancing spectral efficiency at the same time. OFDM’s major issue is the high peaks or peak-to-average power ration (PAPR) that introduced due to summation of subcarriers’ signal. Many methods has been proposed to alleviate this issue however some may increase signal average power. In this paper, a new scrambling method using simple XOR operation is proposed for PAPR and average power reduction in OFDM system